Return to Wyldcliffe Heights : [large type] a novel - Goodman, Carol (Thorndike Press large print dynamic drama, 2024)
"Jane Eyre meets The Thirteenth Tale in this new modern gothic mystery from two-time Mary Higgins Clark Award-winner Carol Goodman, about a reclusive writer who is desperate to rewrite the past. Losing yourself inside of a book can be dangerous. Not everyone finds their way out. Agnes Corey, a junior editor at a small independent publisher, has been hired by enigmatic author Veronica St. Clair to transcribe the sequel to her 1993 hit phenomenon, The Secret of Wyldcliffe Heights. St. Clair has been a recluse since the publication of the Jane Eyre-esque book, which coincided with a terrible fire that blinded and scarred her. Arriving in the Hudson Valley at St. Clair's crumbling estate, which was once a psychiatric hospital for "wayward women," Agnes is eager to ensure St. Clair's devoted fans will get the sequel they've been anticipating for the past thirty years. As St. Clair dictates, Agnes realizes there are clues in the story that reveal the true--and terrifying--events three decades ago that inspired the original novel. The line between fact and fiction becomes increasingly blurred, and Agnes discovers terrible secrets about an unresolved murder from long ago, which have startling connections to her own life. As St. Clair's twisting tale infiltrates Agnes's psyche, Agnes begins to question her own sanity--and safety. In order to save herself, Agnes must uncover what really happened to St. Clair, and in doing so, set free the stories of all the women victimized by Wyldcliffe Heights"--